Effects of mix uniformity in diets with high inclusion of alternative ingredients on growth performance and carcass characteristics in swine and poultry - Morts, Megan (Kansas State University, 2016)
Three finishing pig and one broiler chick experiment were completed to determine the effect of diet formulation, mix time, and diet form on growth performance and carcass measurements. In Exp. 1, finishing pigs fed corn-soy diets had greater ADG, HCW, DP, and BF (P < 0.05) compared to pigs fed diets with 30% DDGS and 10% wheat middlings. However, increasing mix time from 60 to 420 s did not affect growth performance or carcass measurements (P > 0.38). In Exp. 2, pigs were fed diets with 32% DDGS and 32% wheat middlings and were mix for 0, 15, 30, 60, or 420 s. There were no differences in growth performance or carcass measurements as mix time was increased from 0 to 420 s (P > 0.06). In Exp. 3, pigs were fed 32% DDGS and 32% wheat middlings in meal and pelleted diets that were mixed for 0 or 180 s. Pelleting diets increased ADG and improved G/F (P > 0.01). Increasing mix time had no effect on ADG or G/F (P > 0.16) as mix time was increased from 0 to 180 s. There were no differences in carcass measurements because of diet form or mix time. In the final experiment (Exp. 4), broiler chicks were fed a corn-soy diet or a diet with 20% DDGS and 20% wheat middlings and mixed for 0, 15, 30, 60, and 300 s. Broiler chicks fed the corn-soy diet had greater G/F (P < 0.01) but increasing mix time from 0 to 300 s did not affect growth performance or carcass characteristics (P > 0.13). Increased mix time in diets with high levels of alternative ingredients does not affect growth performance or carcass measurements when fed to finishing pigs or broiler chicks.
Keywords: DDGS; middsmix uniformity